ANALISIS PAJAK, KEPEMILIKAN ASING, MEKANISME BONUS, PROFITABILITAS DAN PENGARUHNYA TERHADAP TRANSFER PRICING: Tax, Foreign Ownership, Bonus Mechanism, Profitability, Transfer Pricing - Hendrianto, Samino (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
His study aims to analyze taxes, foreign ownership, bonus mechanisms, profitability and their effect on transfer pricing. The research time period used is 4 years, namely the 2017-2020 period. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 10 companies. The hypothesis testing used is Panel Data Regression Analysis using E-views 9.0 software. The results show that taxes, bonus mechanisms, and profitability have no effect on transfer pricing. Meanwhile, foreign ownership has a negative effect on transfer pricing.